Gambaran Sanitasi Air Minum Isi Ulang (DAMIU) di Kelurahan Lasiana tahun 2019 - Fangidae, Astry Yonitha; Riwu, Yuliana Radja; Ndoen, Honey. I.; Sahdan, Mustakim (Timorese Journal of Public Health, 2019)
Diarrhea problems due to contamination with Escherichia coli bacteria in drinking water depots have become known in Kupang City. This is supported by Telan of the 2015 study in the work area of the Oepoi Community Health Center in the city of Kupang, in which it is found that 20% of the DAMIU are contaminated with E. coli bacteria. This study aims to determine the level of knowledge of the DAMIU operator, the hygiene of the DAMIU devices, the personal hygiene and the description of the bacteriological content in DAMIU in the village of Lasiana in 2019 and also the bacteriological content of drinking water in DAMIU. This research is done at DAMIU in Lasiana Village. The time of the study was carried out from January to July 2019. The population in this study was the total DAMIU in the Lasiana district, which was 21 DAMIU. This study uses a Purposive Sampling technique so that the sample of this study is 10 DAMIU families located in the Lasiana district. The results of this study show that: The total bacteriological content of E. coli that does not meet the requirements is 60% DAMIU. For the renovation of DAMIU devices that do not meet 80% of the requirement. The number of DAMIU operators with a good level of knowledge is 90%. This does not mean good criteria for DAMIU body care. The conclusion is that DAMIU in Lasiana still does not meet the requirements of both bacteriological requirements as well as device hygiene and personal hygiene of the operator. Suggestions for the health office and DAMIU owners to comply with DAMIU hygiene standards more carefully and decisively.